Railroads and Growth in Prussia - Erik Hornung (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
We study the effect of railroad access on urban population growth. Using GIS techniques, we match triennial population data for roughly 1,000 cities in nineteenth-century Prussia to georeferenced maps of the German railroad network. We find positive short- and long-term effects of having a station on urban growth for different periods during 1840–1871. Causal effects of (potentially endogenous) railroad access on city growth are identified using propensity score matching, instrumental variables, and fixed-effects estimation techniques. Our instrument identifies exogenous variation in railroad access by constructing straight-line corridors between nodes. Counterfactual models using pre-railroad growth yield no evidence to support the hypothesis that railroads appeared as a consequence of a previous growth spurt.
Keywords: O18; O33; N73; 330